2021 IEEE Power &Amp; Energy Society Innovative Smart Grid Technologies Conference (ISGT) 2021
DOI: 10.1109/isgt49243.2021.9372264
|View full text |Cite
|
Sign up to set email alerts
|

Event-Based Analysis of Solar Power Distribution Feeder Using Micro-PMU Measurements

Abstract: Solar distribution feeders are commonly used in solar farms that are integrated into distribution substations. In this paper, we focus on a real-world solar distribution feeder and conduct an event-based analysis by using micro-PMU measurements. The solar distribution feeder of interest is a behind-the-meter solar farm with a generation capacity of over 4 MW that has about 200 low-voltage distributed photovoltaic (PV) inverters. The event-based analysis in this study seeks to address the following practical ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…From the MDR results obtained from the statistics T 2 and Q with PCA for the fixed-time approach (2nd column of Tables 2 and 3), the set of twenty-one faults of the Tennessee benchmark problem can be grouped into four subsets according to the level of detection difficulty. Group 1 refers to easy faults (1,2,4,6,7,8,12,13,14); group 2, to intermediate faults (11,17,18); group 3, to hard faults (5,10,16,19,20,21); and group 4, to very hard faults (3,9,15). First, significant MDR gains were verified for eight faults, all related to the Q statistic.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…From the MDR results obtained from the statistics T 2 and Q with PCA for the fixed-time approach (2nd column of Tables 2 and 3), the set of twenty-one faults of the Tennessee benchmark problem can be grouped into four subsets according to the level of detection difficulty. Group 1 refers to easy faults (1,2,4,6,7,8,12,13,14); group 2, to intermediate faults (11,17,18); group 3, to hard faults (5,10,16,19,20,21); and group 4, to very hard faults (3,9,15). First, significant MDR gains were verified for eight faults, all related to the Q statistic.…”
Section: Resultsmentioning
confidence: 98%
“…The authors reported a gain in network security and bandwidth. [12] described an eventbased analysis of a solar distribution feeder integrated into distribution substations. The authors highlighted an improvement in event detection, analysis of the impact of solar production, and understanding of the dynamics of the solar feeder control system.…”
Section: Introductionmentioning
confidence: 99%
“…In [4], visual inspection is used to cross-compare the measurements from micro-PMUs on two different load feeders to identify the local events for each feeder. In [16]- [18], visual inspection is used to investigate the simultaneous impact of specific events, such as lightning strikes, on various components of a power distribution network, such as solar power inverters. For example, they visually verified the results from impedancebased event region identification methods.…”
Section: Literature Reviewmentioning
confidence: 99%
“…This section briefly discusses the conventional impedancebased method [18], [19] to solve the event region identification problem. We apply this method to micro-PMU data from the…”
Section: Limitations Of the Conventional Impedance-based Solutionmentioning
confidence: 99%
See 1 more Smart Citation